2012
DOI: 10.1002/adma.201104372
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Gradient Effect on Energy Bands in Bent ZnO Microwires

Abstract: The table of contents image illustrates the strain-gradient effect on the optical-electronic properties in a bent ZnO microwire, with a much stronger red-shift on the outer tensile side than a blue-shift on the inner compressive side. The low temperature cathodoluminescence cross-sectional scanning spectra on the strain-neutral middle-plane are highlighted by thicker black lines, which clearly shows a strain-gradient induced red-shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 25 publications
7
68
0
1
Order By: Relevance
“…It has been demonstrated that compressive and tensile strains will result in wi dening and narrowing bandgap in CdSe crystal, respectively. The similar conclusion has also been widely demonstrated in other semiconductors [7,[15][16][17][18]21,23,24]. Therefore, an inhomogeneous strain field imposed to CdSe crystal will induce a continuous spatial variation of electronic band structures.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…It has been demonstrated that compressive and tensile strains will result in wi dening and narrowing bandgap in CdSe crystal, respectively. The similar conclusion has also been widely demonstrated in other semiconductors [7,[15][16][17][18]21,23,24]. Therefore, an inhomogeneous strain field imposed to CdSe crystal will induce a continuous spatial variation of electronic band structures.…”
Section: Resultssupporting
confidence: 52%
“…The elastic strain engineering becomes even more important in semiconducting micro/nano-structures because they possess much higher mechanical toughness and strength compared to their bulk counterparts [13,14]. For example, significant energy redshifts of the near-band-edge (NBE) luminescence in uniaxial strain modulated ZnO [15] and GaAs [16] nanowires, as well as in curved ZnO [17][18][19][20] and CdS [21] micro/nanowires have been observed. It has also been reported that the elastic strain-gradient can effectively modulate the photoexcited carrier and exciton dynamics in MoS 2 atomic membrane [7,22] and ZnO micro/ nanowires [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, our investigation demonstrates that the donor-bound exciton drift induced by the elastic strain gradient is the reason of the overall energetic red-shift in bent ZnO micro/ nanowires observed in all previous works. 17,20,21 …”
Section: Resultsmentioning
confidence: 99%
“…For low-dimensional materials, the effect of strain on tuning physical properties becomes enhanced when compared with their bulk counterparts owing to the broader tunable range resulted from the large elasticity when the dimension of a material is scaled down. [7][8][9][10][11][12] For example, the loadable elastic strain of nanomaterials can be approximately reached to their theoretical values, [13][14][15][16][17][18][19][20] which can be increased by 2-3 orders of magnitude higher than their bulk forms. Thus, such a huge difference for the loadable strain between the nanomaterials and their bulk counterparts may bring remarkable changes in physical properties.…”
mentioning
confidence: 99%